The Effects of Human Feeding Activities on Animal Behaviors - Yang, Runyu (Transactions on Environment, Energy and Earth Sciences, 2024)
Human interaction with animals, both domestic and wild, dates to millions of years ago, in ancient times when early humans formed symbiotic relationships with wildlife for survival, which eventually led to the domestication of certain species for food, labor and later companionship. This review essay will focus mainly on human feeding behaviors and their consequential influence on animal species. I would discuss different aspects of the influences with case studies from different research teams to evaluate both the positive and negative impacts and how can we utilize them to improve animal welfare and sustainability. After my review work, I found out that pros and cons come hand in hand in most situations. For example, human feeding behaviors can disrupt animal’s natural behaviors and lead to ecological imbalances. On the other hand, proper feeding behaviors can sometimes reduce the stress levels of animals and improve both their physical and mental health. Going into greater depth with the application of the advantages of human feeding, there are still considerations about whether such an act is ethical since it alters animals’ natural behaviors or if there would be any unknown long-term effect on the animal population. This review article aims to provide insight into how human feeding behaviors can affect animal behaviors so related workers and staff can have a clearer view of their behaviors and the potential consequences.